SPOP Mutations in Prostate Cancer across Demographically Diverse Patient Cohorts - Mirjam Blattner; Daniel J. Lee; Catherine O'Reilly; Kyung Park; Theresa Y. MacDonald; Francesca Khani; Kevin R. Turner; Ya-Lin Chiu; Peter J. Wild; Igor Dolgalev; Adriana Heguy; Andrea Sboner; et al. (Neoplasia: An International Journal for Oncology Research, 2014)
BACKGROUND: Recurrent mutations in the Speckle-Type POZ Protein (SPOP) gene occur in up to 15% of prostate cancers. However, the frequency and features of cancers with these mutations across different populations is unknown. OBJECTIVE: To investigate SPOP mutations across diverse cohorts and validate a series of assays employing high-resolution melting (HRM) analysis and Sanger sequencing for mutational analysis of formalin-fixed paraffin-embedded material. DESIGN, SETTING, AND PARTICIPANTS: 720 prostate cancer samples from six international cohorts spanning Caucasian, African American, and Asian patients, including both prostate-specific antigen-screened and unscreened populations, were screened for their SPOP mutation status. Status of SPOP was correlated to molecular features (ERG rearrangement, PTEN deletion, and CHD1 deletion) as well as clinical and pathologic features. RESULTS AND LIMITATIONS: Overall frequency of SPOP mutations was 8.1% (4.6% to 14.4%), SPOP mutation was inversely associated with ERG rearrangement (P < .01), and SPOP mutant (SPOPmut) cancers had higher rates of CHD1 deletions (P < .01). There were no significant differences in biochemical recurrence in SPOPmut cancers. Limitations of this study include missing mutational data due to sample quality and lack of power to identify a difference in clinical outcomes. CONCLUSION: SPOP is mutated in 4.6% to 14.4% of patients with prostate cancer across different ethnic and demographic backgrounds. There was no significant association between SPOP mutations with ethnicity, clinical, or pathologic parameters. Mutual exclusivity of SPOP mutation with ERG rearrangement as well as a high association with CHD1 deletion reinforces SPOP mutation as defining a distinct molecular subclass of prostate cancer.